The Right of Set-Off as A Way to Settle Accounts Between Entrepreneurs - Michal WOJDALA (Communications of International Proceedings, 2021)
Set-off as a way to cancel debt is an immensely popular way to settle accounts. This applies both to natural persons and (or perhaps most of all) business operators, for whom this form is usually convenient due to its fast-track procedure and no need to incur additional costs. However, sometimes the parties dispute over whether these is debt to be set off between them at all and over how big it is. This article aims to shed light on the subject matter of set-off, done by means of a declaration made out of court (especially the requirements for such declarations provided by generally applicable law for them to be effective) and on a procedural defense of set-off which may occur after the parties to the proceedings enter into a dispute.
Keywords: set-off; defense of set-off; debt cancellation